Antimicrobial effects of terpinen-4-ol against oral pathogens and its capacity for the modulation of gene expression - Bordini, Ester Alves Ferreira [UNESP]; Tonon, Caroline Coradi [UNESP]; Francisconi, Renata Serignoli [UNESP]; Magalhães, Fernando Augusto Cintra [UNESP]; Huacho, Patrícia Milagros Maquera [UNESP]; Bedran, Telma Lombardo; Pratavieira, Sebastião; Spolidorio, Luis Carlos [UNESP]; Spolidorio, Denise Palomari [UNESP] (Taylor & Francis, 2018)
This study evaluated the antibacterial activity of terpinen-4-ol against Streptococcus mutans and Lactobacillus acidophilus and its influence on gbpA (S. mutans) and slpA (L. acidophilus) gene expression. As measured by XTT assay, the concentrations of terpinen-4-ol that effectively inhibited the biofilm were 0.24% and 0.95% for S. mutans and L. acidophilus, respectively. Confocal microscopy revealed the presence of a biofilm attached to the enamel and dentin block surfaces with significant terpinen-4-ol effects against these microorganisms. The expression of the gbpA and slpA genes involved in adherence and biofilm formation was investigated using RT-PCR. Expression of these genes decreased after 15 min with 0.24% and 0.95% terpinen-4-ol in S. mutans and L. acidophilus, respectively. These findings demonstrate the antimicrobial activity of terpinen-4-ol and its ability to modulate the expression of gbpA and slpA genes, emphasizing the therapeutic capacity of terpinen-4-ol as an alternative to inhibit adherence in biofilm.
Keywords: biofilms; Microorganisms; terpinen-4-ol